Evaluation of an early biomarker panel for the identification of emergency department patients at high risk for a short term cardiac outcome - Phan, Kim (My University, 2012)
Patients presenting to the emergency department (ED) with chest pain suggestive of acute coronary syndrome (ACS) often wait long hours before a decision on their care is made. The recommended blood test to aid in diagnosing myocardial infarction (MI) is cardiac troponin I (cTnI) or cardiac troponin T (cTnT). However, other biomarkers representing acute processes and diseases related to ACS might also be useful for early identification. To that end, I evaluated whether a biomarker panel at presentation could improve the diagnostic performance of identifying patients at high risk for MI or any other related cardiac outcome as compared to using cardiac troponin alone. The patient population consisted of 102 patients who presented to the ED with chest pain. Sixteen biomarkers measured in serum obtained at presentation were ranked via receiver-operating-characteristic (ROC) curve analysis for a composite cardiac outcome within the first 72 hours following presentation to the ED. The top four biomarkers (soluble fms-like tyrosine kinase, Creatinine, monocyte chemoattraction protein-1, and NT-pro brain natriuretic peptide) were used to construct the panel test. The ROC derived cutoffs for each of the biomarkers were used to characterize abnormal concentrations with an overall biomarker score incorporating all 4 biomarkers used to classify patients that were either positive or negative for the biomarker panel. When used in conjunction with high-sensitivity cardiac troponin, the panel’s sensitivity and specificity were 100% (95%CI: 75-100%) and 54% (95%CI: 43-65%), respectively. This represented an improvement compared to high-sensitivity cardiac troponin I (hs-cTnI) or hs-cTnT alone which had a sensitivity/specificity of 92% (95%CI: 64-100%)/57% (95%CI: 46-68%) and 85% (95%CI: 55-98%)/55% (95%CI: 44-66%), respectively. In summary, a 4-biomarker blood-based panel used in conjunction with cardiac troponin at ED presentation may identify patients at risk for MI or related outcomes in the short term.
Keywords: Medical Sciences; Medical Sciences